NEPHROPROTECTIVE EFFECTS OF LISINOPRIL IN THE THERAPY OF HYPERTENSIVE PATIENTS WITH OBESITY - S. G. Shulkina; Е. N. Smirnova (Рациональная фармакотерапия в кардиологии, 2018)
Aim. To investigate the dynamics of biomarkers of early renal damage in patients with hypertension (HT) and obesity treated with lisinopril and diet therapy.Material and methods. The study included 120 people aged 25 to 55 years (90 patients with HT in combination with obesity and 30 HT patients without obesity). Control group was consisted of 50 healthy respondents without obesity. All HT patients received therapy with lisinopril at a dose of 10-40 mg per day with titration to target blood pressure (BP) values, patients with obesity – additionally diet therapy. Initially and after 6 months we investigated clinical and biochemical parameters, levels of leptin, resistin, cystatin C in blood serum and urine, albuminuria, NGAL (neutrophil gelatinase associated lipocalin) and interleukin 18 (IL-18) in the urine.Results. We identified the relationships between the serum cystatin C and BP, leptin, resistin, insulin-resistance index (HOMA-IR) and also metabolic indicators. In this study we revealed relationships of subclinical tubular dysfunction markers (urinary cystatin C, IL-18, NGAL) with carbohydrate and lipid metabolism, BP, hormonal activity of adipose tissue. The achievement of target BP values, normoalbuminuria and improving the glomerular filtration rate (GFR) were found after 6 months. The decrease in serum cystatin C in groups was seen: in Group 1 – from 1112 [757.0; 1400.0] to 797 [754; 825] ng/ml (р=0.001), in Group 2 – from 990 [700.0;1110.0] to 791 [770;900] ng/ml (р=0.03). Decrease in markers of tubular dysfunction was identified only in patients who reduced the body weight: urine cystatin C − from 33.0 [18.5; 50.0] to 24[15.3; 60.0] ng/ml (р=0.04) and IL-18 – from 0.33 [0.18; 0.41] to 0.21 [0.14; 0.43] pg/ml (р=0.04). Greater reduction in tubular dysfunction markers excretion was observed in the subgroup of patients with weight loss more than 5% but less than 10% of the initial value.Conclusion. The obtained relationships between markers of subclinical tubular damage and carbohydrate, lipid metabolism and adipokines prove the contribution of adipose tissue to the formation of tubular damage in patients with HT associated with obesity. Antihypertensive therapy with lisinopril contributes to the achievement of target BP values, improvement of metabolic parameters, increase in GFR, achievement of normoalbuminuria, whereas body weight loss in HT patients with obesity additionally contributes to the reduction in the manifestations of tubular dysfunction.